Changing Spatial Patterns of Agriculture in the Punjab Province and the Food Sustainability - Syed Shahid Ali (Journal of Basic & Applied Sciences, 2021)
Pakistan is essentially an agricultural country as most of the population is still living in the rural areas and depending on agriculture for their livelihood. Increasing population is putting more and more pressure on the agricultural lands of the country to fulfill the food requirement. Forty four percent of the labor force of the country is alone shared by agriculture sector. Its importance increases as the most of the industries are also dependent on the agricultural products as their raw material. The province of Punjab is the agricultural hub of the country and playing a vital role in supplying the food grain and other agricultural products not only to the population within the province but to all other parts of the country. The districts in the province are producing the major grain crops, which is quite sufficient for showing the level of sustainability for the population within their limits. Only few districts in the Punjab with highly populated urban centers such as Lahore, Rawalpindi and Islamabad are showing somewhat lower shares of agricultural contribution.